Nematicidal Effects and Cytotoxicity of Levamisole on Thelazia callipaeda - Zhengxuan Han; Yipeng Zhong; Ni Chen; Zichen Liu; Zhankui Yuan; Yipeng Jin (Animals)
Thelazia callipaeda (T. callipaeda) is a zoonotic ocular parasite that poses a public health risk. Current treatment depends on mechanical parasite extraction and specific prophylactic anthelmintics, but direct ocular deworming agents are limited and expensive, and mechanical removal is often incomplete, causing animal stress and ocular injury. Levamisole eye drops have been applied; however, their efficacy and safety remain undefined. We established a standardized T. callipaeda viability assessment system (TVAS) and an animal infection model to evaluate candidate drugs. In vivo, 5 mg/mL levamisole was administered at escalating frequencies. Ocular symptoms, complete blood count (CBC), and serum biochemistry were measured, and cytotoxicity was assessed using Cell Counting Kit-8 (CCK-8) and lactate dehydrogenase (LDH) assays on rabbit conjunctival epithelial cells (RCECs).Four doses of 5 mg/mL levamisole applied at 30 min intervals cleared T. callipaeda from infected eyes within 2 h without significant changes in CBC, serum biochemistry, or ocular symptom scores. CCK-8 and LDH assays indicated minimal cytotoxicity in RCECs within 4 h. However, prolonged exposure (6–12 h) led to a significant decrease in RCEC viability, suggesting potential cytotoxicity with extended use and highlighting the need for further safety evaluation. A regimen of four topical administrations of 5 mg/mL levamisole at 30 min intervals cleared T. callipaeda from infected eyes with minimal cytotoxicity, supporting its safety and efficacy as a topical treatment.